Impact of nanoparticle-based fuel additives on biodiesel combustion: An analysis of fuel properties, engine performance, emissions, and combustion characteristics - Mofijur, M. (2024)
Nanoparticles (NPs) are becoming increasingly crucial in academic as well as industrial applications. Nanoparticles’ addition to biodiesel shortens the time it takes for the fuel to ignite, allowing combustion to begin earlier and reducing the amount of heat released and the pressure in the cylinders under full load. Recent review studies have focused on nanoparticle additives used in biodiesel and diesel engines, performance, combustion behavior, and emission properties of biodiesel-powered diesel engines, and stability and combustion characteristics of metal nanoparticles (NPs) and their additive impact on compression ignition engines powered by biodiesel and diesel. However, nanoparticle effects on either biodiesel properties, engine performance, emissions, or combustion have not been comprehensively investigated in these studies. This paper addresses this gap by focusing on cost-effective and sustainable strategies for the development of fuel additives for biodiesel combustion. The literature has demonstrated that the incorporation of NP mixes (CeO2 + Al2O3) with biodiesel fuel improved the overall performance, emission characteristics, and combustion efficiency of the engine. For instance, the addition of TiO2 nanoparticles reduced smoke emission by 32.98 %, carbon monoxide (CO) by 30 % and unburned hydrocarbons (HC) by 28.68 %. Emissions of nitrogen oxide (NOx), CO, HC, and smoke were reduced by 30 %, 60 %, 44 %, and 38 %, respectively, while brake power (Bp) and brake thermal efficiency (BTE) went up by 12 %. This study will show advances and potential areas for nanoparticle-enhanced biodiesel engine improvement, leading to cost-effective and sustainable renewable energy solutions.